Human rights in women victims of sexual violence in the armed conflict: A systematic review (2022)
The purpose of this article was focused on analyzing the adjacent factors related to human rights in women victims of sexual violence in the context of the armed conflict. The quantitative method of descriptive approach was selected under the systematic review technique using the PRISMA guide. As a result, it was obtained that women continue to be instrumentalized in wars, their physical and psychosocial vulnerability persisting in all spheres of life; This being a phenomenon that continues to growglobally given the characteristics associated with political, social and religious structures. As a conclusion, it was identified that, although there are jurisprudential guidelines and policies, these are insufficient and do not protect the human rights of women victims.